Causes and consequences of shifting cultivation and its alternative in the hill tracts of eastern Bangladesh - Rahman, S.A.; Rahman, M.F.; Sunderland, Terry C.H. (2011)
Shifting cultivation, which is still prevalent in the uplands of eastern Bangladesh, contributes significantly to forest loss and is the main cause of land degradation. This paper presents the causes and consequences of shifting cultivation and its potential land use alternatives. The analysis presented is primarily qualitative with a supplementary quantitative analysis of the causes of forest loss by logistic regression. The results of the study show that traditional land practices, exacerbated by poverty and associated with a lack of technical knowledge is the main cause for the continuation of unsustainable shifting cultivation. Population pressure, inadequate land for cultivation, low education levels, policy planning and implementation without local participation are all factors that influence farmers’ decision to continue shifting cultivation. Intensive land management through agroforestry is a promising alternative that can sustainably manage the remaining forest resources. If adopted, such systems potentially provide good economic returns, and may significantly reduce rural poverty.